Transfer RNA-derived fragment production in calves challenged with Mycoplasma bovis or co-infected with bovine viral diarrhea virus and Mycoplasma bovis in several tissues and blood - Goldkamp, Anna K.; Atchison, Randy G.; Falkenberg, Shollie M.; Dassanayake, Rohana P.; Neill, John D.; Casas, Eduardo (Frontiers in Veterinary Science, 2024)
Understanding the molecular mechanisms underlying immune response can allow informed decisions in drug or vaccine development, and aid in the identification of biomarkers to predict exposure or evaluate treatment efficacy. The objective of this study was to identify differentially expressed transfer RNA-derived fragments (tRFs) in calves challenged with Mycoplasma bovis (M. bovis) or co-infected with M. bovis and bovine viral diarrhea virus (BVDV). Serum, white blood cells (WBC), liver, mesenteric lymph node (MLN), tracheal-bronchial lymph node (TBLN), spleen, and thymus were collected from Control (n = 2), M. bovis (MB; n = 3), and co-infected (Dual; n = 3) animals, and small RNAs extracted for sequencing. An average of 94% of reads were derived from 5` halves and/or 5` tRFs in serum, liver, WBC, TBLN, spleen, MLN, and thymus. The expression of tRFs in lymphatic tissues (MLN, TBLN, Thymus, Spleen) were highly correlated with each other (r ≥ 0.82), but not with serum and WBC. A total of 25 and 65 differentially expressed tRFs were observed in liver and thymus, respectively. There were no differentially expressed tRFs found in other tissues analyzed. Nineteen thymus tRFs were differentially expressed in Dual compared to Control and MB, and the predicted targets of these tRFs were associated with MAPK signaling pathways and ERK1 and ERK2 cascades. The differentially expressed tRFs found in thymus and liver may underlie mechanisms of thymic depletion or liver inflammation previously observed in BVDV. Additional studies should be pursued to investigate differential expression of the predicted tRF targets.